Gender, Parenting, and The Rise of Remote Work During the Pandemic: Implications for Domestic Inequality in the United States. Issue 2 (April 2021) - Dunatchik, Allison; Gerson, Kathleen; Glass, Jennifer; Jacobs, Jerry A.; Stritzel, Haley
We examine how the shift to remote work altered responsibilities for domestic labor among partnered couples and single parents. The study draws on data from a nationally representative survey of 2, 200 US adults, including 478 partnered parents and 151 single parents, in April 2020. The closing of schools and child care centers significantly increased demands on working parents in the United States, and in many circumstances reinforced an unequal domestic division of labor.